Self-Assembly of MnS Shell on CdTe Nanoparticles Induced by Thermohydrolysis: Synthesis and Characterization - Cuevas, Raul Fernando; Prado, Silvio Jose; Solano Reynoso, Victor Ciro [UNESP]; Pradela Filho, Lauro Antonio; Menezes, Pablo Henrique; Balanta, Miguel Angel Gonzalez (Wiley, 2025)
Herein, CdTe/MnS core/shell nanoparticles dispersed in an aqueous solution have been synthesized. The formation of MnS semiconductor shell occurs by spontaneous self-assembly. This process is activated by thermal hydrolysis that removes the excess of thiol and releases S2− ions. In this process, Mn2+ ions on the surface of the CdTe nanoparticles bind to S2− ions to produce a fine semiconducting layer of MnS. Measurements of Raman spectroscopy, optical absorption, and electrochemical measurements are performed. The Raman spectrum shows CdTe characteristic bands at 141 and 163 cm−1. Bands at 221 and 444 cm−1 are associated with the MnS structure. Cyclic voltammetry and differential pulse voltammetry are used to estimate the electrochemical gap at ≈2.47 eV. Absorption optical measurements show tree absorption bands. A broad band between 460 and 520 nm is associated with the first transition in CdTe nanoparticle. The absorption spectrum reveals an optical gap in the range of 2.41–2.33 eV for all the refluxed samples. These values are consistent with those obtained with the electrochemical measurements. The results evidence the formation of a core–shell semiconducting nanostructure made of CdTe nanoparticles coated with a spontaneously self-assembled thin layer of MnS nanoparticles.
Keywords: CdTe; core–shell; MnS; nanoparticles; self-assembly; semiconductor